HAKIKAT DAN SISTEM NILAI DALAM KONTEKS TEKNOLOGI PENDIDIKAN - Murjani Murjani (ADIBA : JOURNAL OF EDUCATION, 2021)
The essence of the value system according to the understanding of paturalism, pragmatism and idealism. a) A value system that is based on Naturalism, is nature-centric (centered on nature), to the physical body, to the five senses, to things that are real; b) Different from naturalism is pragmatism, which is more concerned with its orientation to anthropocentric (human-centered) views, to the human mind, to the ability of creativity and human growth, to practical matters, intelligence abilities, actions in society and to oneself. human (individuality). Thus pragmatism also does not recognize that in humans there is the ability of morality and spirituality, because humans are creatures who depend only on the ability of creativity, intelligence, and ways of doing things in society.